Pengembangan Multimedia Interaktif Berbasis Macromedia Flash pada Materi Sistem Peredaran Darah Manusia Kelas V Madrasah Ibtidaiyah Al-Ikhwan Pekanbaru - Miftah Audhiha; Melly Andriani; Asyti Febliza; Zul Afdal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aimed at describing the validity of Macromedia Flash based Interactive Multimedia on Human Circulatory System material and describing student and teacher responses to Macromedia Flash based Interactive Multimedia on Human Circulatory System material. This research was instigated by the conventional instructional media used by the teacher, and the lack of school facility utilization to support the learning process. It was Research and Development (R&D) with Borg and Gall development model. The subjects of this research were 31 students at the fifth grade of Islamic Elementary School of Al-Ikhwan Pekanbaru in the Academic Year of 2019/2020, and the object was Macromedia Flash based Interactive Multimedia on Human Circulatory System material. Instruments of collecting the data were interview, documentation, validation sheet given to the experts of media and material to measure the validity of Macromedia Flash based Interactive Multimedia on Human Circulatory System material, and questionnaire of teacher and student responses to see teacher and student responses to Macromedia Flash based Interactive Multimedia developed on Human Circulatory System material. The obtained data then were analyzed by using qualitative and quantitative descriptive analysis techniques. Based on the research and data analysis, it could be concluded that Macromedia Flash based Interactive Multimedia on Human Circulatory System material at the fifth grade of Islamic Elementary School of Al-Ikhwan Pekanbaru, especially in the final product developed, passed the valid criterion with mean scores of the assessments of media experts 96% and material experts 94.5%, it was on very good category and it was proper to be tested. After testing, Macromedia Flash based Interactive Multimedia on Human Circulatory System material at the fifth grade of Islamic Elementary School of Al-Ikhwan Pekanbaru showed 100% percentage result for the small group test and 100% percentage result for the field test, and it was on very good category. The result of teacher response to Macromedia Flash based Interactive Multimedia on Human Circulatory System material at the fifth grade of Islamic Elementary School of Al-Ikhwan Pekanbaru was 98.2% percentage, and it was on very good category.